COMPARATIVE EFFICACY OF TOFACITINIB 5 MG BD VERSUS SHORT COURSE ORAL STEROID IN TREATMENT OF ALOPECIA AREATA (The Research of Medical Science Review, 2025)
Background: Non-scarring hair loss marks the autoimmune condition known as alopecia areata (AA). Among current treatments include Janus kinase (JAK) inhibitors such as Tofacitinib and systemic corticosteroids. This trial evaluated in moderate-to-severe AA the safety and efficacy of Tofacitinib 5 mg BD against the short course of oral corticosteroids. Methods: Enrolling 280 individuals, in this cross-sectional research patients were assigned to either tofacitinib 5 mg for 12 weeks (n=140) or oral corticosteroids (0.5 mg/kg/day, tapered over 8 weeks, n=140). Severity of Alopecia Tool (SALT) score at baseline, Week 6 and Week 12 evaluated hair regrowth primarily. Adverse effects, treatment adherence, relapse rates and quality of life (DLQI scores) were secondary outcomes. Results: With SALT reduction of 65.6% against 44.3%, tofacitinib group showed faster response (4.5 ± 1.2 weeks vs. 6.8 ± 1.5 weeks, p < 0.001) and more hair regrowth. With tofacitinib (13.6% vs. 30.0%, p < 0.001), relapse rates were notably reduced. For tofacitinib group (p = 0.002), DLQI improvement was greater. With tofacitinib, treatment adherence—85.7 vs. 70.0%—was better (p = 0.004). The corticosteroid group experienced more frequent adverse effects including weight gain, hyperglycemia and hypertension; tofacitinib demonstrated a better safety profile. Conclusion: Compared to corticosteroids, tofacitinib shown improved tolerance, faster regrowth, lower recurrence rates and greater efficacy. With more study on long-term results and cost-effectiveness, these results supported tofacitinib as the recommended therapy for chronic and treatment-resistant AA.